The description of the di- passive construction in dialectal Javanese - Malihah, Noor (UI Scholars Hub, 2018)
This corpus of the non-standard Kudus dialect of Javanese (JDK) passive voice construction was compiled in the course of fieldwork in Kudus and was annotated to draw attention to several syntactic/semantic features. An investigation was undertaken of the di- affix in the JDK which encodes the passive function in contrast to the Standard Javanese in a quantitative descriptive analysis. The results indicate the existence of an “abbreviated agentive passive” which occurs more frequently than the “agentive passive”, but less frequently than the “agentless passive”. The results also show that the passives in JDK are in fact likely to have inanimate subjects and have only animate demoted agents. However, human demoted agents appear more frequently than animal agents. Also, there is a tendency for the passive without di- to be most likely to be used as an agentless passive. The results suggest that the less colloquial the genre, the less likely the passive without di- is to occur.